One year on from the backlog recovery plan: What next for NHS waiting lists? - Max Warner; Ben Zaranko (Institute for Fiscal Studies (IFS), 2023)
One year ago, NHS England published its plan to tackle the backlog of elective care, which had surged following the onset of the pandemic. Since then, as widely expected, waiting lists for NHS treatment in England have continued to grow, increasing by around 1 million between February and November 2022 to just shy of 7.2 million incomplete treatment pathways. In this report, we examine whether the NHS is on track to achieve the challenging ambitions laid out in its backlog recovery plan and present a number of different scenarios for waiting lists over the next two years.
Keywords: 330; Health and social care; NHS waiting lists; NHS; Healthcare; Health